Age-depth models, magnetic susceptibility, diffuse spectral reflectance, grain size and elemental geochemistry of four sediment cores from the Gulf of San Jorge (Patagonia, Argentina) - Desiage, Pierre-Arnaud; St-Onge, Guillaume; Montero-Serrano, Jean-Carlos (PANGAEA, 2024)
Multiproxy analysis (including magnetic susceptibility, diffuse spectral reflectance, elemental geochemistry and grain size) of five sediment piston cores (COR1404-001PC, COR1404-003PC, COR1404-006PC, COR1404-008PC and COR1404-011PC) in order to characterize the evolution of sedimentary environments and depositional history of the Gulf of San Jorge (Patagonia, Argentina) since the Last Glacial Maximum. The data were collected on board the R/V Coriolis II during the MARGES (Marine Geology of the Gulf of San Jorge) expedition (January 29 to March 4, 2014) as part of the PROMESSe (PROgrama Multidisciplinario para el Estudio del ecosistema y la geología marina del golfo San Jorge y las costas de las provincias de Chubut y Santa Cruz) project. Color reflectance, pXRF and magnetic susceptibility were performed at 1-cm intervals on freshly split core sections using a GEOTEK Multi-Sensor Core Logger. Prior to grain size analysis, the five piston cores were evenly sampled every 8 cm with a refined sampling at 4-cm intervals for basal sections of cores COR1404-003PC, COR1404-006PC and COR1404-008PC. Grain size analysis of sediment samples was carried out on the detrital fraction using a Beckman Coulter LS 13 320 particle size analyser. The age-depth models were generated with radiocarbon ages calibrated using the software CALIB version 7.1, the Marine13 calibration curve and a marine regional reservoir correction (ΔR) of 0. The “best fit” linearly interpolated age-depth models were constructed with the Bayesian statistical approach of the BACON v2.2 package of the R software.
Keywords: Aage depth model; elemental geochemistry; Grain size data; Gulf of San Jorge; Magnetic susceptibility; Patagonia